DUKUNGAN SOSIAL DAN SHYNESS PADA SISWA SMA - Ridfah, Ahmad; Alwi, M. Ahkam (Jurnal Psikologi TALENTA, 2024)
This study aims to analyze the relationship between social support from parents, teachers, and peers with shyness among high school students in Makassar. Shyness is a state of discomfort in social situations that leads individuals to withdraw from interaction. A total of 375 students participated in this study, selected through multistage non-random sampling techniques. Data were collected using a questionnaire consisting of the Child and Adolescent Social Support Scale (CASS) and a shyness scale. The results of the correlation analysis indicate a significant negative relationship between social support from parents, teachers, and peers and shyness. Among these, peer support has the greatest influence in reducing shyness in students. The findings of this study highlight the importance of social support, particularly from peers, in lowering levels of shyness and enhancing students' social interactions.